Post-kala-azar Dermal Leishmaniasis with Mucosal Involvement: An Unusual Case Presentation including Successful Treatment with Miltefosine (Journal of Health, Population and Nutrition, 2013)
Post-kala-azar dermal leishmaniasis (PKDL) is a dermatologic manifestation that usually occurs after visceral leishmaniasis (VL) caused by Leishmania donovani. It is characterized by hypopigmented patches, a macular or maculopapular rash and nodular skin lesions on the body surface. Involvement of the mucosae is very rare and unusual in PKDL. We report a case of PKDL that presented with polymorphic skin lesions, along with involvement of peri-oral mucosa and tongue from an endemic area for kala-azar in Bangladesh. In the absence of a definite past history of kala-azar, a clinical suspicion for PKDL was confirmed by positive rapid serological tests against two recombinant (rK39 and rK28) leishmanial antigens, demonstration of Leishmania donovani (LD) body in the slit skin smear, and isolation of promastigotes by culture from a nodular lesion. The patient was treated with oral Miltefosine for three consecutive months and showed significant clinical improvement as demonstrated by a negative slit skin smear at two months after initiation of therapy. We report this case as an unusual presentation of mucosal involvement in PKDL and subsequent treatment success with Miltefosine. J HEALTH POPUL NUTR 2013 Jun; 31(2): 294-297 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16395